Weaving Pictures: 15th Century Tapestry Production at Lengberg Castle - Nutz, Beatrix; Ottino, Claudia (Archaeological Textiles Review, 2013)
This article, based on finds made during an archaeological investigation carried out at the Lengberg Castle, East-Tyrol, explores the possibility of small scale tapestry production at castles of the minor nobility in the medieval period. Seven finds could de identified as textile tools, two of which were used for weaving. A tapestry bobbin and a pin beater suggest tapestry production. This article introduces the technique of tapestry and the use of a tapestry bobbin. It describes the tapestry bobbin and pin beater from Lengberg in detail, together with the results of the botanical analyses. Comparable finds from Great Britain and Denmark are considered and the proper function of a bobbin is examined. The extent to which tapestry production took place at Lengberg is discussed, who could have been employed in it, and what the results of this study signify with respect to possible tapestry production at other small castles in Europe.